Lung aspergillosis in an adult woman - Yanara Toledano Grave de Peralta; Martha Campos Muñoz; Serguei Silveria Digón (Centro Provincial de Información de Ciencias Médicas, 2016)
The case report of a 44 years mixed race patient from an urban area is described, with a personal history of alcoholic liver disease who was admitted in the Pneumology Service of "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital in Santiago de Cuba, after being referred from her health area due to expectoration episodes with blood and dry cough.  Laboratory studies, sputum culture, thorax X rays, lung computerized axial tomography and fine-needle aspiration biopsy were carried out that lead to the mycetoma diagnosis due to Aspergillus fumigatus, which facilitated to indicate the appropriate treatment and to carry out the clinical follow up of the affected patient.